ARMI 2.0: An online risk management simulation - Pontakorn Sonchan (2018)
© 2015 IEEE. Risk management is an important area in software engineering. An effective risk management process positively influences project success. ARMI is a physical card game which simulates risk management in software engineering. During the simulation, participants follow principles of risk management and aim to complete the cycles while economizing their expenses. ARMI 2.0 aims to improve shortcomings in the original such as difficulties in calculation of costs and semi-predetermined randomization as well as enhance user experiences. The development and experimental results of this enhanced simulation are described and discussed in this paper.